THE IMPACT OF RESTORATIVE JUSTICE ON ADDRESSING JUVENILE OFFENSES THE IMPACT OF RESTORATIVE JUSTICE ON ADDRESSING JUVENILE OFFENSES - Aisyah, Sitti; Fahrudin, Muhammad Husni (Sekolah Tinggi Ilmu Hukum Awang Long, 2024)
Restorative justice has emerged as a promising alternative to traditional punitive systems on a global scale, particularly in the context of addressing juvenile crime. This article explores the effectiveness of restorative justice in responding to child crime by analyzing its core principles, implementation strategies, and outcomes. Employing a blend of qualitative and quantitative research methods, the study delves into case studies, interviews with stakeholders, and statistical data from jurisdictions that have adopted restorative justice practices. The findings indicate that restorative justice can effectively reduce recidivism rates, promote community reintegration, and improve the psychological well-being of both offenders and victims. However, the research also highlights challenges, including inconsistent application and cultural barriers that can impede its effectiveness. To address these issues, the paper offers several recommendations, such as standardizing policies, enhancing facilitator training, and fostering community engagement to optimize the impact of restorative justice initiatives.